Mini-Open Carpal Tunnel Release Technique - Mitrović, Mihajlo (Halo 194 Scientific Journal of Emergency Medicine, 2021)
Carpal tunnel syndrome is the most common cause of upper extremity compressive neuropathy. It is more commonly present in females, in the middle-aged population and is a significant socioeconomic problem. More than 500 000 patients are surgically treated yearly in the USA, which costs more than 4 billion dollars. Since the middle of the 20th century, severe and medium severe cases are primarily treated surgically. Until the introduction of endoscopy, the dominant surgical method was classic open surgery. The objective of the paper is to examine the efficacy, safety and economic value of the mini-open carpal tunnel release technique using a vertical 2cm long cut in the carpal region. From January 2018 to December 2019, we performed 35 carpal tunnel decompressions on 30 patients using the mini-open carpal tunnel release technique and standard surgical scissors. There were no intraoperative complications. All patients were night-pain free from the very first day after surgery. Pillar pain, incision pain and hand weakness were progressively becoming less pronounced during the next 12 weeks. At the final check-up, only one patient still had pronounced symptoms that required a reintervention. The rest of the patients had completely recovered. Even though the endoscopic procedure for carpal tunnel decompression is constantly evolving, the classic open method and newly developed mini-open carpal tunnel release technique remain the treatments of choice. Our research shows that the mini-open carpal tunnel release technique is a quick, efficient, safe and cheap surgical technique for treating carpal tunnel compressive neuropathy.